Implementasi Metode Sorogan Dalam Meningkatkan Pola Berpikir Santri PPAI Darun Najah Malang - Sidiq, Mukhammad Nur Iman; Sirojudin, Didin (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to find out how the implementation of the sorogan method in improving the mindset of students at PPAI Darun Najah Ngijo Karangploso Malang and to find out the supporting factors and inhibiting factors for this implementation. This study used a qualitative method where the data obtained came from research documents, interviews, observations and documentation. Data analysis techniques take three steps which include data reduction, data presentation and drawing conclusions. . The results of the study show that: 1) the implementation of the sorogan method is very important and effective in improving the thinking patterns of students in the current era. 2) Supporting factors and inhibiting factors for the sorogan method are sometimes internal and external as follows: 1) Supporting factors sometimes include internal factors including the strong self-interest of the students, motivation of the students, seriousness of the students and the physical condition of the students and external factors including caregivers, competence of the teacher, students seniors, peers, environment, residence and time. 2) Inhibiting factors are sometimes internal factors including laziness, compulsion of students, not learning and illness and external factors including the absence of teachers, supervision and attention of senior students, peers and difficulty discussing.